Non-formal adult education using experimental science activities - Oliveira, Clara Costa (2016)
In Portugal, the University of Minho train non-formal adult for more than 25 years, promoting the empowerment of populations and stimulating intervention and change in their communities. In this way we have introduced experimental science in a logic of increasing scientific literacy of target audiences, as well as differentiation of usual animation models, usually with strong idadist prejudices. The following four of these projects streamlined with different groups of adults, namely elders users of a nursing home (two different situations), war veterans and illegal drug consumers. The experimental activities, games and demonstration, with strong visual and kinesthetic components, carried out within the mentioned populations were: (i) analysis of photosynthetic pigments of the nursing home’s environmental surroundings and observing enlarged details (SEM photographs - Scanning Electron Microscopy) (ii) atherosclerosis (symptoms, risk behaviours, care) and building models simulating the deposition of cholesterol in the arteries; (iii) the sea as a means of communication and support of biodiversity and (iv) observation of the night sky (stars and constellations) and construction of a sundial. The realization of these projects involved specific training of non-formal adult educators, carried out by group STOL (Science Through Our Lifes) devoted to communication and dissemination of science, an articulation between the sciences of education and the natural sciences. Methods and theoretical principles of construction of this type of knowledge by the target population resided however in non-formal adult education, understood as life long learning and education. The most commonly methods were: group dynamics, role-playing, PBL (Problem-Based Learning) and life narratives. All the activities have been subjected to ongoing evaluation and adjusted accordingly to it